Carbon credit of renewable energy projects in Malaysia - Lim X.; Lam W.H.; Shamsuddin A.H. (Institute of Physics Publishing, 2023)
The introduction of Clean Development Mechanism (CDM) to Malaysia improves the environment of the country. Besides achieving sustainable development, the carbon credit earned through CDM enhances the financial state of the nation. Both CDM and renewable energy contribute to the society by striving to reduce carbon emission. Most of the CDM projects are related to renewable energy, which recorded 69% out of total CDM projects. This paper presents the energy overview and status of renewable energies in the country. Then, the renewable energy will be related to the CDM. Published under licence by IOP Publishing Ltd.